International Human Rights Law and Islamic Law Related To The Protection Of Migrant Workers In Indonesia In The Perspective Of Mashood A. Baderin - Moh Miftahul Hasan Badrus Shomad; Muh Nur Misuari; Muhammad Hasan Saifur Rijal; M Khoirul Hadi al asy ari (Fakultas Hukum Universitas Islam Indonesia, 2025)
One of the biggest contributors to foreign exchange in the country of Indonesia is Indonesian migrant workers, but often Indonesian migrant workers receive inhumane treatment. Therefore, this research aims to protect migrant workers related to human rights and Islamic law, more specifically the views of Mashood A. Baderin. There are two important questions in this research: first, how is the concept of international human rights law and Islamic law from the perspective of Mashood A. Baderin? Second, how is the idea of international human rights law and Islamic law, according to Mashood A. Baderin, and its relevance in protecting Indonesian migrant workers? This research uses normative and qualitative methods based on a literature study or library research. In contrast, the analysis method uses the content analysis method to explain the concept of international human rights law and Islamic law from the perspective of Mashood A. Baderin and its relevance in protecting Indonesian migrant workers. The results of this study are to first know the concept of international human rights law and Islamic law from the perspective of Mashood A. Baderin and to know the idea of international human rights law and Islamic law according to Mashood A. Baderin and its relevance in the protection of Indonesian migrant workers.